LIFE AND WORK OF CARLOS LINNEAEUS - Cid Martínez, Marcela Alejandra (Kuxulkab’, 2024)
Carlos Linnaeus was born in the city of Råshult, Sweden on May 23, 1707, the son of a Lutheran pastor, who had a weakness: a love for plants. Linnaeus was expected to follow in his father’s footsteps, and he did, just not for the spiritual side. After the intervention of a local doctor, Linnaeus began his studies in this field, which allowed him to continue his interests (botany). He carried out explorations outside his native Sweden to know and order plants, he published, he taught at the University of Uppsala, he was internationally recognized at the age of 31 and for his contributions to science he received honors and distinctions. His masterpiece written by him practically during the 18th century was undoubtedly his «natural system» in the twelfth edition he described in round numbers 15,000 species. Following Linnaeus’s death on January 10 the 1778, Sir James Edward Smith purchased his collections and founded the Linnean Society of London (1788).